EFEKTIVITAS GEL LIDAH BUAYA (Aloe vera) TERHADAP PENYEMBUHAN KETOMBE KERING di Madrasah Aliyah Negeri 2 Ponorogo - Dewi Puspita Ningrum; Hery Ernawati; Laily Isro'in (Universitas Muhammadiyah Ponorogo, 2018)
AbstractDandruff is often regarded as a mild thing. However, for patients it resulted in disruption of comfort and confidence. The use of natural ingredients without the side effects of chemicals for the treatment of dry dandruff is by using traditional materials obtained from the natural surroundings, one of which is aloe vera (Aloe vera). Aloe vera (Aloe vera), which chemically has elements of a compound that can replace chemical drugs to cope with dry dandruff such as phosphorus, vitamins A, B, amino acids, saponins and flavonoids. The design of this study using one group pra-post test design, with a population of 23 respondents, a sample of 23 respondents, using total sampling technique. Collecting data using questionnaires. Data processing with data normality test pre-post 30%, then using a paired t-test with significance 0.05.The results of this study obtained from 23 respondents, 17 respondents (73.9%) experienced a decline in scores, 4 respondents (17.4%) score remained, and 2 respondents (8.7%) decrease increase of dry dandruff score. Statistical analysis showed significant results with a p-value = 0.000 0.05. The conclusion of this study is aloe vera gel (Aloe vera) has an effect to healing dry dandruff. Therefore it is expected that sufferers of dry dandruff are more selective to choose the type of scalp treatment.Keywords: Aloe Vera Gel, Dry Dandruff.AbstrakKetombe kering sering dianggap sebagai hal yang ringan. Namun, bagi penderita hal tersebut mengakibatkan gangguan kenyamanan dan tidak percaya diri. Penggunaan bahan alami tanpa menimbulkan efek samping untuk pengobatan ketombe kering adalah dengan menggunakan bahan tradisional, salah satunya adalah lidah buaya (Aloe vera). Lidah buaya (Aloe vera) yang secara kimia memiliki unsur-unsur senyawa yang dapat menggantikan fungsi obat kimia untuk mengatasi ketombe kering diantaranya fosfor, vitamin A,B, asam amino, saponin dan flavonoid. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian gel lidah buaya (Aloe vera) terhadap penyembuhan ketombe kering. Desain penelitian ini menggunakan one group pra-post test design, dengan jumlah populasi 23 responden, sampel 23 responden, dengan menggunakan teknik total sampling. Pengumpulan data menggunakan kuesioner. Pengolahan data dengan uji normalitas data pre-post 30%, maka menggunakan uji paired t-test dengan kemaknaan 0,05. Hasil penelitian ini didapatkan dari 23 responden, 17 responden (73,9%) mengalami penurunan skor, 4 responden (17,4%) skor tetap, dan 2 responden (8,7%) mengalami penurunan peningkatan skor ketombe kering. Analisis statistika menunjukkan hasil yang signifikan dengan nilai = p-value 0.000 0.05. Kesimpulan dari penelitian ini adalah gel lidah buaya (Aloe vera) mempunyai efek untuk penyembuhan ketombe kering. Maka dari itu diharapkan penderita ketombe kering lebih selektif untuk memilih jenis perawatan kulit kepala.Kata Kunci : Gel Lidah Buaya, Ketombe Kering.